Some population parameters of the lessepsian suez puffer (lagocephalus suezensis) from iskenderun bay, northeastern mediterranean, Turkey - Başusta, Asiye; Başusta, Nuri; Özer, Ebru I.; Girgin, Hulya; Aslan, Ergun (My University, 2013)
In this study the length-weight relationships (LWRs), length-length relationships (LLRs) and relative condition factor were determined for Lagocephalus suezensis captured in the Gulf of Iskenderun, northeastern Mediterranean Sea. Sampling was carried out by commercial bottom trawls using at 24 and 50 meters depths during August and December 2012. The population of Suez puffer fish showed the expected ratio of 1:1. The exponent b values were 2.6764±0.0025 for male and 2.9144±0.0019 for female and 2.7946±0.0014 for sexes combined of L. suezensis. The coefficient of determination (R2) was significant for all individuals. The types of growth for both sexes were negative allometric growth for L. suezensis. The LLRs between the three length measurements (total length, fork length, standard length) were highly correlated(R2>0.9527). Relative condition factor (Krel) ranged from 1.165±0.009 (for male) to 1.169±0.009 (for female). This study presented the first reference on LLRs and condition factor for Lessepsian puffer from NE Mediterranean coast of Turkey. © 2013 Zoological Society of Pakistan.
Keywords: Condition factor; Lagocephalus suezensis; Length-length relationships; Length-weight relationships; Lessepsian puffer; North-eastern Mediterranean Sea